オーストラリア セイガン オキ ノ タイリク シャメン ニ オケル タイセキソウ コウゾウ ニ ツイテ - 堀田, 宏; ホッタ, ヒロシ; HOTTA, Hiroshi (国立極地研究所, 1969)
P(論文) The continuous seismic reflection profiling was made in 1965-1966 during the 7th Japanese Antarctic Research Expedition This paper reports on the structure of sediments on the continental slope along the west coast of the Australian continent, as a part of the results The pneumatic gun of Lament Geological Observatory type was used as the sound source The ship's track is given in Fig 1 Photographic records are presented in Figs 3, 4, 6 and 8. Line drawings from these photographic records are presented in Figs 5, 7, 9 and 10 In these pictures, horizontal distances are given in terms of the ship's navigation time One hour navigation of the ship gives approximately 22km of distance, as the ship ran at a rate of 12 kt during the observation Depths of the sea bottom and each reflector are given in two way reflection travel time in seconds. The whole area of observation is divided into three regions depending on the character of structure of sediments Each region is numbered from the north to the south. Schematic illustrations of Fig. 11 show the character of structure of sediments in each region This division may not have practically any geological significance, since there is only one profile running parallel to the continental slope of the Australian continent departmental bulletin paper